Prevalence of diabetic retinopathy and vision loss in the Beijing Eye Study: the potential role of the cerebrospinal fluid pressure - Jonas, Jost B. (Current diabetes reports, 2015)
In the Beijing Eye Study, a population-based study carried out in 2001, 2006, and 2011, prevalence of diabetic retinopathy (DR) was 2.9 ± 0.3 % (95 % confidence interval 2.3, 3.5) per individual in 2011. Correspondingly, only 1.1 % of blindness and 0.8 % of visual impairment were caused by DR in East Asia. As in other populations, prevalence, severity, and 10-year incidence of DR were associated with higher levels of HbA1c, higher blood glucose concentration, longer known duration of diabetes, lower educational level, and higher blood pressure. Interestingly, the presence, severity, and 10-year incidence of DR were additionally correlated with higher estimated cerebrospinal fluid pressure and shorter ocular length. Higher cerebrospinal fluid pressure may lead to higher retinal vein pressure and subsequently higher retinal capillary blood pressure increasing fluid and blood extravasation. Shorter axial length or hyperopia may be associated with higher intraocular concentration of cytokines. Aging of the society, improvements in medical infrastructure, and lifestyle changes may profoundly increase prevalence of, and burden by, DR in China in the future.